Influence of Polymer Molecular Weight on in-vitro Characteristics and Cytotoxicity of Fulvestrant Loaded Nanoparticles - Hascicek, Canan; T. Sengel-Turk, Ceyda; Gumustas, Mehmet; A. Ozkan, Sibel; Bakar, Filiz; Das-Evcimen, Net; Savaser, Ayhan; Ozkan, Yalcin (Current Drug Therapy, 2014)
The objective of this research was to fabricate a novel polymeric nanoparticulate system of Fulvestrant (FLV) and investigate the effect of polymer molecular weight variation on in vitro properties and also anti-proliferative potency of the carriers. Two different forms of polymerspoly( lactic-co-glycolic acid) (PLGA) were employed for the fabrication of polymeric nanoparticles (PNPs) by using a combination of diffusion-emulsification-salting out preparation procedure. In vitro evaluation of the PNPs was performed in terms of entrapment efficiency, particle size, surface charge, thermal behavior redispersibility ability, in vitro drug release profile, release mechanisms, stability and anti-proliferative activity. PNPs were obtained in the size range between 191.80 to 211.80 nm with a lower polydesipersity index. FLV release from the developed PNP formulations was more than a 45 days period. Zero order release was obtained with low molecular weight form of PLGA PNPs, while relatively high weights of PLGA PNPs followed square root of time (the Higuchi's pattern) dependent release. Additionally, stability studies showed that PNPs were stable at 4°C for a six months period. In the experimental work, it was also observed that FLV, which was entrapped into the PNPs, displayed strong in vitro antiproliferative activity on MCF-7 human breast cancer cells for a 48 h period, when compared to free the form of FLV. As a conclusion, the PNPs developed in this research may have the potential to deal with the major handicaps of the available IM form of FLV, and may be a new promising delivery preparation approach.
Keywords: PLGA nanoparticles